Virtual Reality Applications in Education - Vivi Melinda; Andree Emmanuel Widjaja (International Transactions on Education Technology (ITEE), 2022)
Virtual reality (VR) is a computer-based simulation technology that enables users to interact while experiencing oneself in a virtual environment.Virtual reality (VR) combines three-dimensional (3D) objects combined with hearing and vision to create effects for users as if they were in a virtual environment. It should be noted here that the use of Virtual Reality is very effective in the field of education Given that a user can observe things in cyberspace from all angles, including above, below, to the left, right, back, and ahead, the 3D coordinate system used in virtual reality (VR) is based on the Cartesian coordinate system.